2006
DOI: 10.1177/0193945905282354
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Chronic Obstructive Pulmonary Disease Readmission in Taiwan

Abstract: This study examines the relationships among physiological, psychological, and social factors and hospital readmission to develop a model predicting chronic obstructive pulmonary disease (COPD) readmission for 145 patients with COPD following hospital discharge at 14 days and 90 days in Taiwan. Daily functioning, comorbidity, severity of illness, self-efficacy, depressive symptoms, and perceived informal support were regressed on hospital readmission. Daily functioning was the only significant variable to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 52 publications
(46 reference statements)
1
31
0
3
Order By: Relevance
“…Nine studies examining the prospective associations between clinical levels and symptoms of psychological distress and exacerbation risk for patients with COPD [9,10,[23][24][25][26][27][28][29] were recently evaluated in a review paper [8]. Three of those studies evaluated outpatients [23][24][25], whereas one included a cohort of elderly medical patients including non-COPD patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies examining the prospective associations between clinical levels and symptoms of psychological distress and exacerbation risk for patients with COPD [9,10,[23][24][25][26][27][28][29] were recently evaluated in a review paper [8]. Three of those studies evaluated outpatients [23][24][25], whereas one included a cohort of elderly medical patients including non-COPD patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…To date, seven prospective longitudinal studies have assessed the association between levels of regular physical activity and hospital admission or readmission due to COPD exacerbations [30,113,[141][142][143][144][145]. All studies consistently showed a statistically significant association of low physical activity levels with increased risk of hospitalisations.…”
Section: Effect Of Physical Inactivity On Hospitalisations In Patientmentioning
confidence: 99%
“…Although all studies reported associations adjusted for confounders, just one study adjusted for previous COPD hospitalisations, which is one of the most important risk factors for readmission [146]. Importantly, the studies have shown that the amount of regular physical activity needed to obtain a significant effect on admissions due to COPD is relatively small, equivalent to walking or cycling for 2 h per week [30,113,[141][142][143][144][145].…”
Section: Effect Of Physical Inactivity On Hospitalisations In Patientmentioning
confidence: 99%
“…На сегодняшний день взаимосвязь между уровнем регулярной ФА и частотой госпитализаций при обострениях ХОБЛ изучалось в 7 проспективных продольных исследованиях [30,113,[141][142][143][144][145] и во всех показана стабильная достоверная взаимосвязь низкой ФА с повышением риска госпитализаций. Несмотря на то, что результаты скорректированы по сопутствующим факторам, только в 1 исследовании корректировка производилась еще и по частоте предшествующих направлений в стационар по пово ду ХОБЛ, которые являются важнейшим фактором повторных госпитализаций [146].…”
Section: влияние низкой фа на частоту госпитализаций у больных хоблunclassified
“…Несмотря на то, что результаты скорректированы по сопутствующим факторам, только в 1 исследовании корректировка производилась еще и по частоте предшествующих направлений в стационар по пово ду ХОБЛ, которые являются важнейшим фактором повторных госпитализаций [146]. Продемонстриро вано, что объем регулярной ФА, необходимый для получения доказательств достоверного влияния на частоту госпитализаций у пациентов с ХОБЛ, доста точно невелик и эквивалентен ходьбе пешком или езде на велосипеде в течение 2 ч в неделю [30,113,[141][142][143][144][145].…”
Section: влияние низкой фа на частоту госпитализаций у больных хоблunclassified